The Balancing Profits and Environmental Responsibilities the Role of Carbon Emission Disclosure On Corporate Sustainability - Ratiningsih Ratiningsih; Diamond Ika Ambarwati; Wulan Budi Astuti (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2025)
ABSTRACT [Times New Roman, 9 Bold, 1 Spacing and italic] The growing issue of climate change has heightened the demand for carbon emissions transparency, particularly among companies that contribute to carbon emissions. However, previous research has shown inconsistent results regarding the factors influencing carbon emissions disclosure, creating a research gap. This study aims to analyze the influence of profitability, leverage, and environmental performance on carbon emissions disclosure. The research method uses a quantitative approach with panel data in the form of annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange for the period 2022-2024. The analysis was conducted using panel data regression with a Fixed Effect Model (FEM). The results show that profitability has a significant influence on carbon emissions disclosure, while leverage and environmental performance do not. Simultaneously, these three variables do not have a significant effect. This finding suggests that the ability to generate profits is more likely to encourage companies to disclose emissions than other structural and environmental factors.